Decoration of Ag Nanoparticle on ZnO Nanowire by Intense Pulsed Light and Enhanced UV Photodetector - Youngwook Noh (MDPI AG, 2021)
Zinc oxide (ZnO) nanowires (NWs) are wide-bandgap semiconductors that absorb ultraviolet (UV) radiation. Various post-treatment processes have been studied to improve the optical properties of the as-grown ZnO NWs. Among them, Ag nanoparticles (NPs) effectively improved the optical properties on the surface of the ZnO NWs. In this study, ZnO NWs were synthesized via the hydrothermal synthesis method. ZnO NWs were decorated with Ag NPs on the surface of the ZnO NWs in a silver nitrate (AgNO3) aqueous solution by intense pulsed light (IPL) irradiation. Ag NPs were successfully decorated under the following conditions: aqueous AgNO3 solution of 100 nM, an energy of 1 J/cm2, and an exposure time of 8 ms. The responsivity and sensitivity of the ZnO NW UV photodetectors increased by 7.43 and 3.37 times, respectively. The IPL process makes it possible to decorate Ag NPs in a simple manner within an extremely short time.